Does one size fit all at all times? The role of country specificities and state dependencies in predicting banking crises - Stijn Ferrari; Mara Pirovano (National Bank of Belgium, 2016)
Given the indisputable cost of policy inaction in the run-up to banking crises as well as the negative side effects of unwarranted policy activation, policymakers would strongly benefit from earlywarning thresholds that more accurately predict crises and produce fewer false alarms. This paper presents a novel yet intuitive methodology to compute country-specific and state-dependent thresholds for early-warning indicators of banking crises. Our results for a selection of early-warning indicators for banking crises in 14 EU countries show that the benefits of applying the conditional moments approach can be substantial. The methodology provides more robust signals and improves the early-warning performance at the country-specific level, by accounting for country idiosyncrasies and state dependencies, which play an important role in national supervisory authorities' macroprudential surveillance.
Keywords: C40; E44; E47; E61; G21; 330; Banking crises; Early warning systems; Country-specific thresholds; State-dependent thresholds